Next Generation Sequencing is the Impetus for the Next Generation of Laboratory‐Based Genetic Counselors. Issue 4 (17th January 2014) - Swanson, Amy; Ramos, Erica; Snyder, Holly
Abstract: Next generation sequencing (NGS) is dramatically increasing the number of clinically available genetic tests and thus the number of patients in which such testing may be indicated. The complex nature and volume of the reported results requires professional interpretation of the testing in order to translate and synthesize the meaning and potential benefit to patients, and genetic counselors are uniquely suited to provide this service. The increased need for genetic counselors in this role, coupled with the time required and a limited number of trained and available counselors presents a challenge to current models for making genetic testing available to patients and their healthcare providers effectively and efficiently. The employment of genetic counselors at genetic/genomic laboratories is one model to expand the resources for providing this service. In this article, we briefly review the advent of NGS and its clinical applications, examine the core skills of genetic counselors and delineate the expanding roles and responsibilities of laboratory‐based genetic counselors. We also propose changes to the genetic counseling training program curriculum to account for the increasing opportunities for genetic counselors to contribute and thrive within genetic testing laboratories.